A Retrospective Review of Diabetic Nephropathy Patients During Referral to the Sub-Urban Nephrology Clinic - Menon, Rena; Mohd Nor, Fariz Safhan; Draman, Che Rosle; Seman, Mohd Ramli; Abdul Ghani, Azril Shahreez (Saudi Center for Organ Transplantation, 2012)
ABSTRACT. Diabetic nephropathy (DN) has become the most common cause of end-stage renal failure.Early referral and specific nephrology treatment could delay the disease progression and should reduce the treatment cost, mortality and morbidity rate in these patients. This is a single-center, retrospective review of all DN patients referred to the nephrology clinic in Hospital Sultan Ahmad Shah, Temerloh, from 2000 to 2009, to study and define the clinical characteristics of DN patients at the time of the referral to the nephrology clinic. A total of 75 patient case records were reviewed. Forty-three (57.3%) of them were males, with a median age of 64.3 ± 8.5 years at the time of referral. Only 14.7% of them had blood pressure lower than 125/75 mmHg. Co-morbid and disease-related complications were also commonly diagnosed and 28.4% (n = 21) had ischemic heart disease, 23% (n = 17) had diabetic retinopathy and 20.3% (n = 15)had diabetic neuropathy. The mean serum creatinine at the time of referral was 339.8 ± 2.3 μmol/L,gylcated hemoglobin A 1c (HbA1C) was 8.1 ± 2.0 %, serum fasting glucose was 9.6 ± 4.7 mmol/L, serum cholesterol was 5.4 ± 1.2 mmol/L and hemoglobin level was 10.6 ± 2.9 g/dL. Although female patients were less frequently seen in the early stages of chronic kidney disease (CKD), they comprised at least 72.7% of CKD stage 5 (male:female; 6:16, P <0.05). Twenty-nine percent (n=22) of them were referred at CKD stage 5, 48% (n=36) were at CKD stage 4, 17.3% (n=13) were at CKD stage 3, 4% (n=3) were at CKD stage 2 and 1.3% (n=1) was at CKD stage 1. Advanced CKD patients were frequently prescribed with more antihypertensives. CKD stage 5 patients were prescribed with two-and-half types of antihypertensive as compared to two types of anti-hypertensive in CKD stage 2 and stage 3. Furthermore, ACE-inhibitors (ACE-I) were less frequently prescribed to them. Only 22.7% (n=5) of CKD stage 5 patients received ACEI and 30% (n=11) in CKD stage 4 patients as compared to 53.4% (n=7) in CKD patients stage 3. This review shows that DN patients were referred late to the nephrologists and the overall disease management was suboptimal. Antihypertensive requirement was also increased and ACEIs were less frequently prescribed in the advanced diabetic nephropathy patients.